Virtual World and Quests Creation on MEGA World (Multiplayer Educational Game for All) (International Conference on Computers in Education, 2019)
A multiplayer online role-play game (MORPG), called MEGA World (MEGA stood for Multiplayer Educational Game for Assessment in v1.0 back to 2010 and now stands for Multiplayer Educational Game for All), has been designed and developed since 2010. MEGA World is a web-based massively multiplayer educational game platform which supports any languages and is capable of access any existing external resources (e.g., multimedia, materials, online meetings, etc.)(Chang & Kinshuk, 2010[1]). Teachers can create their virtual worlds as well as create learning and assessment activities (i.e., quests in the game) of different learning subjects for students' for instances English, and Java Programming, Flash ActionScript, research methods (Kuo, Chang, Kinshuk, & Liu, 2010[2]; Li, Zou, Xie, Wang, & Chang, 2018[3]; Lu, Luo, Chang, Kuo, & Li, 2018[4]; Xu, Chang, Chen, Chen, & Kinshuk, 2016[5]). Students can learn specific knowledge and reach the learning goal by taking and solving those quests while playing. The current version of MEGA World[6] (Multiplayer Educational Game for All) is v2.1 and supports eight quest types for teachers to create: greeting, item collection and delivery, sorting, treasure hunting and digging, calculation, fill-in-the-blank, short answer, and speaking-based conversation quest type (Chang, Chen, Wu, & Yu, 2019[7]). In this version of the game, students can have their own avatars and see others visually. In this tutorial, we are going to show participants how to use MEGA World as well as teach participants how to create virtual worlds, NPCs, quests (individual quest and quest chain) and their quest items and rewards for their courses or learning topics.